THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER VALUE ON INPATIENT SATISFACTION AT BHAYANGKARA HOSPITAL PALU CITY - Razak, Abd; Miru, Sulaeman; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2021)
This study aims to determine the effect of service quality and customer value on inpatient satisfaction at Bhayangkara Hospital Palu City. The type of research was descriptive – verification. The research sample was inpatients at Bhayangkara Hospital Palu, which was determined by the purposive sampling method and totaled 105 patients. This study applied a multiple linear analysis method using SPSS software version 23. The results of this study indicate that (1) service quality and customer value have a significant effect on inpatient satisfaction at Bhayangkara Hospital Palu City, (2) service quality has a significant effect on inpatient satisfaction at Bhayangkara Hospital Palu City, ((3) customer value has a significant effect on inpatient satisfaction at Bhayangkara Hospital Palu City. Keywords: Service Quality, Customer Value, Patient Satisfaction